(untitled) (International Journal of Natural Sciences, 2012)
Clinical and histopathological studies were carried out with juvenile common carp (C. carpio) from a Government fish farm and a NGO fish farm in Mymensingh area for a period of 9 months from April 2005 to December 2005. Clinically red spots, scale loss, weak body, hemorrhage and subcutaneous lesion were noticed especially during November and December. A moderate pathological change in the investigated organs of all fishes were recorded in summer season (April-May), whereas in rainy season (June-July) pathological symptoms were significantly reduced which was again increased to some extent in the autumn season (August-September). However, marked pathological changes such as necrosis, protozoan cyst, bacterial colony, vacuum, melanomacrophase, hemorrhage, hypertrophy, hyperplasia and clubbing were recorded in all the investigated organs like skin, muscle, gill, liver and kidney in the months of October, November and December. Among the affected organs gills were more affected with the presence of numerous protozoan cysts followed by skin, liver and the less affected organ was the muscle. Clinically and histopathologically juvenile common carp of Government fish farm were more affected compare to NGO fish farm especially in colder moths of the year. DOI: http://dx.doi.org/10.3329/ijns.v1i4.9732 IJNS 2011 1(4): 77-81